The Burdens of Occupational Heat Exposure-related Symptoms and Contributing Factors Among Workers in Sugarcane Factories in Ethiopia: Heat Stress Wet Bulb Globe Temperature Meter - Mitiku B. Debela; Achenef M. Begosaw; Negussie Deyessa; Muluken Azage (Elsevier, 2023)
Background: Heat stress is a harmful physical hazard in many occupational settings. However, consequences of occupational heat exposure among workers in a sugarcane factory in Ethiopia are not well characterized. This study aimed to assess the level of occupational heat exposure-related symptoms and contributing factors. Methods: In this cross-sectional study, five workstations were selected for temperature measurement. Heat stress levels were measured using a wet-bulb globe temperature index meter. A stratified random sampling technique was used to select 1,524 participants. Heat-related symptoms were assessed using validated questionnaires. Results: The level of occupational heat exposure was 72.4% (95% CI: 70.2%-74.8%), while 71.6% (95% CI: 69.3%-74.9%) of participants experienced at least one symptom related to heat stress. The most common heat-related symptoms were swelling of hands and feet (78%), severe thirst (77.8%) and dry mouth (77.4%). The identified risk factors were a lack of reflective shields (AOR: 2.20, 95% CI: 1.53, 3.17), not-enclosed extreme heat sources (AOR: 1.76, 95% CI: 1.23, 2.51), a lack of access to shade (AOR: 9.62, 95% CI: 6.20, 14.92), and inappropriate protective clothing provision (AOR: 1.58, 95% CI: 1.27, 2.71). Conclusions: The burden of occupational heat exposure and heat-induced symptoms was high. Lack of reflective shields, the absence of enclosed extreme heat sources, a lack of access to shade, and inappropriate protective clothing provision were considerable attributes of heat stress. Therefore, the use of mechanical solutions to stop heat emissions at their sources and the key factors identified were areas for future intervention.